CCN3, POSTN, and PTHLH as potential key regulators of genomic integrity and cellular survival in iPSCs - Swaidan, Nuha T.; Soliman, Nada H.; Aboughalia, Ahmed T.; Darwish, Toqa; Almeshal, Ruba O.; Al-Khulaifi, Azhar A.; Taha, Rowaida Z.; Alanany, Rania; Hussein, Ahmed Y.; Salloum-Asfar, Salam; Abdulla, Sara A.; Abdallah, Abdallah M.; et al. (Frontiers in Molecular Biosciences, 2024)
Reprogramming human somatic cells into a pluripotent state, achieved through the activation of well-defined transcriptional factors known as OSKM factors, offers significant potential for regenerative medicine. While OSKM factors are a robust reprogramming method, efficiency remains a challenge, with only a fraction of cells undergoing successful reprogramming. To address this, we explored genes related to genomic integrity and cellular survival, focusing on iPSCs (A53T-PD1) that displayed enhanced colony stability. Our investigation had revealed three candidate genes CCN3, POSTN, and PTHLH that exhibited differential expression levels and potential roles in iPSC stability. Subsequent analyses identified various protein interactions for these candidate genes. POSTN, significantly upregulated in A53T-PD1 iPSC line, showed interactions with extracellular matrix components and potential involvement in Wnt signaling. CCN3, also highly upregulated, demonstrated interactions with TP53, CDKN1A, and factors related to apoptosis and proliferation. PTHLH, while upregulated, exhibited interactions with CDK2 and genes involved in cell cycle regulation. RT-qPCR validation confirmed elevated CCN3 and PTHLH expression in A53T-PD1 iPSCs, aligning with RNA-seq findings. These genes’ roles in preserving pluripotency and cellular stability require further exploration. In conclusion, we identified CCN3, POSTN, and PTHLH as potential contributors to genomic integrity and pluripotency maintenance in iPSCs. Their roles in DNA repair, apoptosis evasion, and signaling pathways could offer valuable insights for enhancing reprogramming efficiency and sustaining pluripotency. Further investigations are essential to unravel the mechanisms underlying their actions.